1999
DOI: 10.1089/rej.1.1999.2.43
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Age Changes in Brain and Liver Enzymes of Senescence-Accelerated Mice (SAM)

Abstract: Editor's Note: The SAM (senescence accelerated mouse) model has been used in various aspects of aging research and JAAM has published work on this area previously (see HosoL·wa et al., l:l;[27][28][29][30][31][32][33][34][35][36][37]. The current study attempts to clarify some of the changes which occur in aging cells with the brain and liver of such a model. The particular approach here is to understand how enzymes which affect free radical metabolism alter over the lifespan of the aging animal. ABSTRACTThe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…There are several senescence-prone strains (SAMP), which live 12-15 months, and several senescence-resistant (SAMR) strains, which are normal controls for accelerated aging and have a life span of 24-30 months. It has been shown that SAMP mice develop normally until the age of 4 months and then they reveal signs of accelerated aging (such as loss of hair, skin ulceration, decrease of locomotor activity, deficiency in learning and memory, emotional disorders, abnormal circadian rhythms, brain atrophy, hearing impairment, cataracts, increased production of reactive oxidation specimens (ROS) and 8-hydroxyguanine levels in all organs (40)(41)(42)(43)(44)). The amount of Cu, Zn-SOD in the mitochondria fraction of the SAMP-1 was only half that of the SAMR-1 (45).…”
Section: Senescence Accelerated Mice (Sam)mentioning
confidence: 99%
“…There are several senescence-prone strains (SAMP), which live 12-15 months, and several senescence-resistant (SAMR) strains, which are normal controls for accelerated aging and have a life span of 24-30 months. It has been shown that SAMP mice develop normally until the age of 4 months and then they reveal signs of accelerated aging (such as loss of hair, skin ulceration, decrease of locomotor activity, deficiency in learning and memory, emotional disorders, abnormal circadian rhythms, brain atrophy, hearing impairment, cataracts, increased production of reactive oxidation specimens (ROS) and 8-hydroxyguanine levels in all organs (40)(41)(42)(43)(44)). The amount of Cu, Zn-SOD in the mitochondria fraction of the SAMP-1 was only half that of the SAMR-1 (45).…”
Section: Senescence Accelerated Mice (Sam)mentioning
confidence: 99%